Comparison of Four Lymph Node Staging Systems in Gastric Adenocarcinoma after Neoadjuvant Therapy – A Population-Based Study - Hongkun, Lai; Jiabin, Zheng; Yong, Li (Frontiers in Surgery, 2022)
Introduction:Preoperative treatment leads in a reduction in positive lymph nodes and examined lymph nodes(ELN), which may affect assessment of lymph node staging and postoperative treatment.We aimed to compare the staging of lymph node ratio(LNR), the positive logarithm ratio of lymph nodes(LODDS), negative lymph nodes(NLN), and the 8th AJCC ypN stage for patients with gastric adenocarcinoma after neoadjuvant therapy. Materials and Methods: Data was collected from the Surveillance, Epidemiology, and End Results database and 1551 patients with gastric adenocarcinoma who underwent neoadjuvant therapy and radical surgery were enrolled. Harrell's concordance index, the Receiver Operative Curve, the likelihood ratio test, and the Akaike information criterion were used to compare the predictive abilities of the different staging systems. Results: Among the 1551 patients, 689 (44.4%) had ELN<16 and node-negative patients accounted for 395 (25.5%). When regarded as the categorical variable, LNR had better discrimination power, higher homogeneity, and better model fitness for CSS and OS compared to other stage systems, regardless of the status of ELN. When regarded as the continuos variable, LODDS outperformed others for CSS. Furthermore, the NLN stage system performed superior to others in node-negative patients. Conclusions: LNR had a better predictive performance than ypN, LODDS and NLN stages regardless of the status of ELN when regarded as the categorical variable, whereas LOODS became the better predictive factor for CSS when regarded as the continuos variable. In node-negative patients, NLN might be a feasible option for evaluating prognosis. A combination of LNR and NLN should be considered as user-friendly method in the clinical prognostic assessment.